Meaning negotiation of LEP learners in communicative tasks - Chui, Catherine Lam Nguoi; Azian Abd Aziz @ Ahmad, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
This study aims to explore Limited English Language Proficiency (LEP) learners’ meaning negotiation in communicative tasks. In particular, the frequency of meaning negotiation (MN), types and frequency of MN trigger as well as participants’ perceptions of the communicative tasks in relation to their L2 language development were explored. A total number of 8 participants were engaged in both open and closed communicative tasks designed for the purpose of this study. Data from stimulated recall interviews and structured interviews were used to consolidate the primary data. It was found that the closed communicative task can yield greater meaning negotiation compared to open communicative task. Meaning negotiation in closed communicative task was mainly triggered by task complexity and lexical difficulties, which might be due to the task design. Meanwhile, meaning negotiation in the open communicative task was mainly caused by the delivery of vague message. It was found that meaning negotiation can be a potential platform to facilitate language development among learners, particularly through clarification requests which can create the linguistic urgency to push LEP learners to expand their interlanguage. Thus, ESL teachers might want to equip LEP learners with effective meaning negotiation strategies, particularly clarification requests, to better equip these learners with the skills to modify their language output during communicative tasks.